Pengaruh Pemberian Air Perasan Bawang Daun (Allium fistulosum L.) Terhadap Daya Bunuh Larva Nyamuk Culex sp. - Mega Silvia Anggraini Sukri; Andreas Putro Ragil Santoso; Alfri Danti Izky Oktavia; Fadlillah Triasmoro Iskandar; Ary Andini (PROSIDING NATIONAL CONFERENCE FOR UMMAH, 2020)
The Culex mosquito acts as a vector for elephantiasis or is called filariasis. As an efforts tostop a chain of mosquito spread. The eradication by using chemicals could endanger human health.Therfore, need to make natural insecticides from plants. The aims of study is to determine the effect ofsqueezed water leek (Allium fistulosum L.) to inhibit of Culex sp mosquito larvae. The research was anexperimental method with a complete randomized design. As a control group used without squeezedwater leek, intervention group divided into 10% and 20% concentrations of squeezed water leek. Eachgroup was done with 9 times repetition. Ten Culex mosquito larvae put into each glass of concentration0%, 10%, 20% of squeezed water leek for 24 hours. Afterwards, dead larvaes were counted. Theresults of study showed the mortality of Culex sp mosquito larvae for about 0,56 ± 0,72% for controlgroup, 3,78 ± 0,66% for 10% concentration of leek juice, 5,22 ± 1,20 % for 20% concentration ofsqueezed water leek. Based on the result of Kruskal-Wallis test, showed there were a significant effect,between concentration of squeezed water leek to inhibit a larvae mosquito live, with P value 0,000.While the results of Mann-Withney test for each group showed P value < 0,05. The conclusion of thestudy was, consentration of squeezed water leek (Allium fistulosum L.) had a killing power effectCulex sp. Mosquito larvae.